2003
DOI: 10.1002/dir.10064
|View full text |Cite
|
Sign up to set email alerts
|

At the movies, on the Web: An investigation of the effects of entertaining and interactive Web content on site and brand evaluations

Abstract: An experiment was conducted to examine the effects of including entertaining and/or interactive content on evaluations of automotive Web sites and automotive brands. Research participants visited and evaluated four Web sites from major automotive manufactures. The four sites exhibited varying degrees of entertaining content and interactivity. The highly entertaining site (which included a mini, suspenseful movie) was associated with the most positive site evaluations, greatest intent to return to the site, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(118 citation statements)
references
References 28 publications
4
109
0
5
Order By: Relevance
“…These results are confi rmed by other studies ( Ducoffe, 1996 ;Brackett Ferrazzi, Chen and Li (2003) found that entertaining games in combination with sales messages can encourage dialogs with customers and project product images. Online advertising that is enriched with entertaining elements achieves a more positive evaluation by recipients and leads to higher intent to revisit the homepage than web sites without entertainment features ( Raney et al, 2003 ).…”
Section: Results Of Hypotheses Testsmentioning
confidence: 99%
“…These results are confi rmed by other studies ( Ducoffe, 1996 ;Brackett Ferrazzi, Chen and Li (2003) found that entertaining games in combination with sales messages can encourage dialogs with customers and project product images. Online advertising that is enriched with entertaining elements achieves a more positive evaluation by recipients and leads to higher intent to revisit the homepage than web sites without entertainment features ( Raney et al, 2003 ).…”
Section: Results Of Hypotheses Testsmentioning
confidence: 99%
“…Studies also link the presence of entertaining content to effectiveness. For example, Raney et al (2003) find that including a mini-movie on an automotive website is the most effective method of boosting purchase intention. These results suggest that approaches that are both interactive and entertaining create excitement and have a spillover effect on the brand, regardless of whether a push or pull strategy is employed.…”
Section: Branding Building Effectmentioning
confidence: 99%
“…Furthermore, recent studies demonstrated that satisfying the need for autonomy in video games increases enjoyment, the desire for future game play, game recommendations, and game ratings (e.g., Przybylski, Rigby, and Ryan 2010;Tamborini et al 2010;Peng et al 2012;Neys, Jansz, and Tan 2014). Recent research has shown that the positive associations and feelings gained from the game, such as game enjoyment and the desire for future game play, can transfer to the brand depicted in the game, increasing consumers' brand attitude (van Reijmersdal, Rozendaal, and Buijzen 2012;Raney et al 2003). This effect is commonly known as the spill-over effect (e.g., Wise et al 2008;Nelson, Yaros, and Keum 2006).…”
Section: Theoretical Background Effects Of Advergame Customization Onmentioning
confidence: 99%
“…Advergames are free and simple digital games (Redondo 2012) specifically designed to promote a brand, product, service, or idea (Terlutter and Capella 2013). In general, advertisers employ these games to reach two goals: first, by providing consumers the opportunity to 'play with' the brand, they hope that the positive associations and feelings gained from the game transfer to their own brand, increasing consumers' brand attitude (van Reijmersdal, Rozendaal, and Buijzen 2012;Raney et al 2003). Second, since players are regularly asked to register to play (Lee and Youn 2008), advergames serve as a powerful asset for building brand loyalty and for collecting data about potential and existing customers (Youn and Lee 2005;Steel 2013;Çeltek 2010).…”
Section: Introductionmentioning
confidence: 99%